Pengaruh Bakteri Pelarut Fosfat terhadap Pertumbuhan dan Hasil Kedelai pada Pertanaman Kelapa Sawit TM-I - Cucu Suherman; Arya Hanif Nugroho; Mochamad Arief Soleh (Paspalum: Jurnal Ilmiah Pertanian, 2023)
Wide space among oil palm Mature Stage I (MS  I) plantations has a potential to be planted with soybean by using intercropped system. One type of soil in oil palm plantations in Indonesia is Inceptisol which generally has low P availability. Efforts possible to increase P availability are the applications of inorganic P fertilizer and phosphate solubilizing bacteria (PSB). This study aims to learn the effects of various inorganic P fertilizer and PSB doses on the growth and yield of soybean in oil palm MS I plantation and determine the effects of intercropping soybean on the growth and physiology of oil palm MS I. The research was conducted at Ciparanje Experimental Field, Faculty of Agriculture, Universitas Padjadjaran, from February to May 2023. The study used randomized block design with seven treatments and four replications. Treatment consisted of different doses of Bacillus sp. and SP36 which included: 100% SP36, 50 kg/ha PSB + 25% SP36, 50 kg/ha PSB + 50% SP36, 50 kg/ha PSB + 75% SP36, 75 kg/ha PSB + 25% SP36, 75 kg/ha PSB + 50% SP36, and 75 kg/ha PSB + 75% SP36. Results showed PSB and P fertilizer had a significant effect on the dry weight of 100 seeds and leaf chlorophyll index of soybean. Dose of 50 kg/ha PSB + 50% SP36 increased the dry weight of 100 seeds by 3,99% and leaf chlorophyll index by 15,35%.